A prospective comparative study on the operative outcomes between monopolar versus bipolar transurethral resection of prostate for benign prostatic hyperplasia: An institutional experience - Pogula, Vedamurthy Reddy; Galeti, Ershad Hussain; Kanchi V, Bhargava Reddy (Asian Journal of Medical Sciences, 2021)
Background: Benign prostatic hyperplasia (BPH) is a common disease in elderly men. Monopolar transurethral resection of prostate (M-TURP) is considered the gold standard for the treatment of bladder outlet obstruction due to BPH. Its modification, bipolar TURP (B-TURP), promises to overcome its most prominent drawbacks, such as bleeding and dilutional hyponatremia. Aims and Objectives: This study aims to study the feasibility, effectiveness, and safety of B-TURP over M-TURP. Materials and Methods: A total of 110 patients with BPH were prospectively randomly assigned to undergo B-TURP (55) or M-TURP (55). Patient characteristics of the two groups were similar. Hemoglobin was measured preoperatively and postoperatively. IPSS, maximal flow rate, and post-void residual urine volume were assessed preoperatively. Duration of surgery, mean weight of resected tissue, mean irrigation fluid used, mean drop in hemoglobin, mean change in sodium, and mean post-operative irrigation used were also compared. Results: Duration of resection time was significantly shorter in M-TURP (P=0.0034). The mean change in sodium and mean post-operative irrigation used were significantly lower in bipolar group with P<0.05 and 0.0024, respectively. The mean drop in post-operative hemoglobin concentration (P=0.0916) was statistically insignificant. There was one instance of the transurethral resection (TUR) syndrome in the M-TURP group whereas no TUR syndrome occurred in the B-TURP group. Conclusion: B-TURP and M-TURP are effective and safe techniques for the surgical treatment of BPH. B-TURP definitely reduces the incidence of dilutional hyponatremia and post-operative irrigation use making it a competitor to replace M-TURP as the new gold standard.